ظواهر تراثيَّة في ديوان "تلويحة الأيدي المتعبة" لممدوح عدوان - يسير, خالد عمر (مجلة جامعة تشرين للبحوث والدراسات العلمية- سلسلة الآداب والعلوم الانسانية, 2014)
يتناول البحث الظواهر التراثيَّة في ديوان "تلويحة الأيدي المتعبة" للشاعر"ممدوح عدوان" التي استمدَّها ا من الموروث الديني، مـثـل استــدعاء شخصيَّة "علي بن أبي طالب" (ا)، ومن الموروث التاريخي، مثل استدعاء شخصيَّة "صلاح الدين الأيُّوبي" ، ومن الموروث الأدبي، مثل استدعاء شخصيَّة "الحطيئة"، و"المتنبِّي" وغيرهم. ويبيِّن الباحث حضور التراث في شعر عدوان عن طريق الـتناص مع الـقـرآن الكريم، ومع الشعر، ويبيِّن تأثُّر لـغـة الديوان بلغة التراث، ويتناول أيضاً توظيف الشاعر للتراث في ديوانه المدروس، ويخلص إلى نتائج ذكرت في موضعها من البحث. This research deals with the phenomena of heritage in the Divan of "Brandishing of Tired Hands" of the poet , "MamdouhAdwan" which he drew from the religious heritage , such as calling the figure "Ali bin AbiTalib" , and from the historical heritage, such as calling the figure "Saladin" , and the literary heritage , such as calling the figure "Alahtaih" and "Al-Mutanabbi" and others. Researcher shows the presence of heritage in the poetry of Adwan by intertextuality with the Koran , and with poetry, and shows influenced language of the divan by the language of heritage , and also addresses the poet's employment of the heritage in his divan, and concludes the results reported in its place of the research